Why Foresters should Care about Social Sector Schemes-Case of Ghumsur Forests of Ganjam District of Odisha - Paul, Shashi (Indian Forester, 2017)
Ganjam was the northernmost district of Madras Presidency during the British Raj. In the year 1936 major part of Ganjam district was merged with newly formed Orissa province. This was the only area with Sal forests in whole of the Madras presidency. British government set its attention on forest resources of the district after 1850. Though efforts to earn profit started in 1851 but forest management took shape with the beginning of 20th century as systematic management under working plans started. To see the impact of forest management, period of nearly 100 years has been taken into consideration i.e. 1920-2015. This can be divided into three phases. From 1920-1990 the major systems of working were selection (for hilly and inaccessible areas) and coppice (for relatively plain and accessible areas). The latter was for meeting needs of local people while former was aimed at commercial timber production. From 1990 onwards coppice system has been discontinued as coppice areas have degraded. With small exceptions, all coppice areas have been moved to rehabilitation areas in the working plans after 1990s. To see the effect of discontinuing of coppice system and rehabilitation treatment for about two decades the situation from 2013 onwards (third phase) has been analysed. It is seen that none of the rehabilitation area has improved. Rather more areas have moved from selection to rehabilitation working circle. Thus stopping coppice system which was fulfilling local needs has not helped to regenerate the forests as whether officially supplied or not forests bear the brunt of local needs. It appears that this is a vicious circle i.e. forests are unable to supply local needs silviculturally but ever increasing population is putting more and more pressure on the forests. Result is degradation of more and more areas gradually in spite of lot of efforts by the Forest Department to rehabilitate the areas. Under such circumstances social sector schemes replacing fuel wood and kutcha houses etc. looks the only hope to reduce the pressure to regenerate the degraded forests. Though not many studies are available but very few available studies also support this contention. Thus foresters should make all possible efforts to link the social sector schemes with their conservation efforts to get the desired results.